Pelatihan Pembuatan Pupuk Cair Organik Dari Limbah Nasi Berekstrak Sereh pada Kelompok Tani Pembibitan Tanaman Bunga dan Buah Lubuk Minturun - Muhammad Zulfikar Luthfi; Ferry Ikhsandy; Agung Kurnia Yahya; Hibrah Hibrah; Harmiwati N. H; Renold Ramadhan Putra (Politeknik ATI Padang, 2022)
The agricultural sector is one of the main pillars of the economy in Koto Tangah District. Increasing agricultural production requires the support of fertilizer availability in terms of quantity and price. In order to provide fertilizer at competitive prices, fertilizers are needed at low prices and are environmentally friendly. This community service activity is given to the community in Lubuk Minturun Village in the form of training in the manufacture of liquid organic fertilizer (POC) with a fermentation process and extracts of lemongrass. The main ingredient of this fertilizer is rice waste which can be easily collected by local people. The training covers the process of making fertilizer, the fermentation process to packaging. Lemongrass extract is added to increase nutrients in the soil and reduce odors from the fermentation process. The proposing team took this theme in order to provide an alternative for making POCs to the community in Lubuk Minturun Village in the hope of contributing to local flower or fruit plant nurseries. In this case, the proposing team took Lubuk Minturun Village as a model because this area is located close to the ATI Padang Polytechnic Campus, so that it can help the lives of the people around the campus.